Debt-Related Vulnerabilities and Financial Crises - Setser, Brad (Occasional Papers; Occasional Paper ;, 2005)
The analysis of currency and maturity mismatches in sectoral balance sheets has increasingly become a regular element in the IMF's tool kit for surveillance in emerging market countries. This paper describes this so-called balance sheet approach and shows how it can be applied to detect vulnerabilities and shape policy advice. It also provides a broad-brushed overview of how balance sheet vulnerabilities have evolved over the past decade and cites a number of case studies.